Angular dependences of ellipsometric parameters of thin Cr and Ti films under surface polariton excitation - Shybiko, Ya.A.; Shaykevich, I.A.; Melnichenko, L.Yu. (Functional Materials, 2006)
The 80 Å and 100 Å thick Cr films and 45 Å thick Ti ones were obtained bу the vacuum evaporation on glass substrates. The ellipsometric parameter ψ (azimuth of the restored linear polarization ψ) was measured at λ = 546.1 nm both at the air side and the glass one under various angles of incidence. In the second case, the surface polaritons were excited using the Kretchman method bу means of a transparent semi-cуlinder. Parameters measured at the air side were used to calculate optical constants n and k. Ellipsometric parameters under surface polariton excitation were calculated. The obtained theoretical results conform to the experimental data. The last fact testifies that the Airу formulas can be used to calculate both ellipsometric parameters and reflection and transmission coefficients under surface polariton excitation.